Exilio, insilio, cárcel y violencia: 1948-1952 - Chacón-Araya, German (2017)
In this essay we aim to approach the fate of thousands of Costa Ricans from beginning of 1948 to 1952. This period is marked by the launch of an open political repression against the adversaries of the self-proclaimed Ejército de Liberación Nacional [Army of National Liberation], that entered the capital city at the end of April 1948. This analysis goes up to the year 1952, when most of the political exiles returned to the country as a result of new democratic conditions.